2019
DOI: 10.15446/revfacmed.v67n2.68878
|View full text |Cite
|
Sign up to set email alerts
|

Determinación de endogamia mediante método de isonimia en la población de Runta, Boyacá, Colombia

Abstract: Determinación de endogamia mediante método de isonimia en la población de Runta, Boyacá, Colombia Determination of inbreeding by isonymy in the population of Runta, Boyacá, Colombia INVESTIGACIÓN ORIGINAL | Resumen | Introducción. Dado el hallazgo de enfermedades raras de herencia recesiva en un número mayor de pacientes al esperado, estudios recientes han sugerido la presencia de un aislado poblacional en la vereda de Runta, en el departamento de Boyacá, Colombia. Esto indica la probabilidad de una tasa de co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Gómez et al 10 suggested consanguinity as a cause for the high presence of MPS in Boyacá. Pacheco‐Orozco et al 35 analyzed the high incidence of rare diseases in this department, finding that there is indeed an increased inbreeding rate and therefore this population may be genetically isolated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gómez et al 10 suggested consanguinity as a cause for the high presence of MPS in Boyacá. Pacheco‐Orozco et al 35 analyzed the high incidence of rare diseases in this department, finding that there is indeed an increased inbreeding rate and therefore this population may be genetically isolated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, patients have more possibilities of being transferred to a medical center or sending their samples to a nearby laboratory under optimal conservation and time conditions. G omez et al 10 suggested consanguinity as a cause for the high presence of MPS in Boyac a. Pacheco-Orozco et al 35 analyzed the high incidence of rare diseases in this department, finding that there is indeed an increased inbreeding rate and therefore this population may be genetically isolated.…”
Section: Distribution and Incidence Of Mps In Colombiamentioning
confidence: 99%